English Studies in India: A Critical Survey of Selected Issues: Exploring the Challenges and Solutions in English Studies in India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Effective teaching and learning of English has always seemed to be an evasive prospect in the Indian scenario attributable to the inconceivable complexities that characterize the socio-political and economic nature of the country. Additionally to the present, India‘s unique cultural and linguistic convolutions aggravate matters further posing challenges in English studies that have emerged as relentless and insurmountable from the time English was introduced because the medium of instruction in 1835. Although India succeeded in liberating itself from the foreign rule, the prominent position that English had acquired for itself globally by the center of the 20th century made it impractical and unreasonable to renounce the language at the time of independence. However, several crucial problems associated with English studies that existed during the colonial times persist till date, invalidating a gamut of solutions proposed to beat them, both in the pre and post-independence eras. These issues include the literature-language divide, the English-mother tonguenative language divide, canon formation, marginalisation et al. it's also been observed that the modern educational philosophies of the West fail to supply appropriate assistance in resolving the predicament as they rarely take under consideration the standard nature of Indian classes and situations. On the contrary they result in greater confusion, giving rise to factions of stakeholders sporting divergent opinions on these issues. the current work seeks to conduct a purely theoretical research into the history of English studies in India to critically survey the events, policies, the philosophical, social, political and other aspects and diverse assorted views connected with the teachinglearning of English in India. An attempt is additionally made to research whether this discordant viewpoints will be yoked together for the event of enhanced techniques and policies conducive to ground level improvements in the field. The aim of the research is thus to check the introduction and development of English studies in India critically so as to grasp the issues involved and suggest viable solutions to deal with these issues by attempting to harness conflicting perspectives.